1995
DOI: 10.1002/j.2161-0045.1995.tb00436.x
|View full text |Cite
|
Sign up to set email alerts
|

The Origins of Children's Career Aspirations: IV. Testing Hypotheses from Four Theories

Abstract: In a study of 949 elementary students, mixed support was found for four theoretical positions concerning the role of childhood in career development. For Ginzberg's theory, support was found for his observation that interests play the major role in both the selection and rejection of careers throughout the period of childhood. For Roe's theory, the authors found evidence that family configuration influenced occupational choice/no choice. From Havighurst's theory, support was found for the idea that identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 31 publications
3
77
2
2
Order By: Relevance
“…Surveys verify International Journal of Social Science Research ISSN 2327-5510 2013 the theory proposed by Gottfredson (1996), who examined how children's career preferences evolve and found that children aged between nine and thirteen years have become aware of social status and tend to view less prestigious occupations negatively (Henderson et al, 1988;Trice et al, 1995;Teig & Susskind, 2008). Another study found that children are aware of the different responsibilities between men and women and the differences in wages in occupations defined by gender (Levy et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Surveys verify International Journal of Social Science Research ISSN 2327-5510 2013 the theory proposed by Gottfredson (1996), who examined how children's career preferences evolve and found that children aged between nine and thirteen years have become aware of social status and tend to view less prestigious occupations negatively (Henderson et al, 1988;Trice et al, 1995;Teig & Susskind, 2008). Another study found that children are aware of the different responsibilities between men and women and the differences in wages in occupations defined by gender (Levy et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Work by Lent and others (1994) provide the value of repeated practice, modeling, and feedback based on significant others that foster children to "develop skills, adopt personal standards, estimate their abilities, and form beliefs about likely outcomes of performing certain tasks" (p. 89). For instance, there has been substantiation for the critical role of parents and the influence of family relations in children's career development (Trice, Hughes, Odom, Woods, & McClellan, 1995), the influence of social valuation on children's occupational aspirations (Helwing, 2001) and the decreasing role of fantasy and the increasing realism in occupational aspiration as children develop.…”
Section: Introductionmentioning
confidence: 99%
“…During this period, career choices are driven by the desire to ascend into adulthood (Super, 1953). With their parents being their closest and most accessible adult models at this point in their lives, children's career choices are most heavily influenced by their parents' advice and occupations (Sedofia, 2014;Trice, 1995). At this point in their lives, children's career ambitions have no grounding in reality.…”
Section: Career Development Theoriesmentioning
confidence: 99%
“…While the tentative period is segmented into four stages, a majority of the attention is placed on individuals' interests over any of the other stages (Trice, 1995). The final period, realistic (ages 17 through 24), is the act of actually going through the career development process and making a career choice (Sedofia, 2014).…”
Section: Career Development Theoriesmentioning
confidence: 99%
See 1 more Smart Citation